Return Saham Syariah pada Perusahaan JII: Analisis Pengungkapan Environmental Social Governance dan Kebijakan Dividen - L. L., Dinda Indri; Eliza, Any; Pratomo , Dimas (Indonesian Journal of Islamic Economics and Business, 2025)
This study aims to analyze the effectiveness of Environmental, Social, and Governance disclosure and dividend policy on stock returns of companies included in the Jakarta Islamic Index for 2020–2023. The research employs a quantitative approach by utilizing secondary data, gathered through purposive sampling, resulting in 11 companies that consistently released annual and sustainability reports throughout the observation period, resulting in 44 observations. The panel data regression technique was employed for data analysis, with model selection guided by the results of the Chow test, Hausman test, and Lagrange Multiplier (LM) test. To ensure the validity of the estimated model, classical assumption diagnostics, including checks for multicollinearity and heteroscedasticity. The results show that ESG disclosure has no significant influence on stock returns. The dividend policy, as measured by the Dividend Payout Ratio (DPR) has a significant and negative influence on stock returns. Simultaneously, ESG disclosure and dividend policy have a significant influence on stock returns.